Dampak Latihan Anaerobik Terhadap Aktivitas Sistem Saraf Otonom: Literature Review - Lopo, Yusuf Nikodemus (Universitas Singaperbangsa, 2022)
The autonomic nervous system is a control system in the body such as respiration, digestion and heart rate. The autonomic nervous system always works when a person is sleeping or doing activities. In exercise also the autonomic nervous system plays an important role. Anaerobic training is an exercise activity that does not require oxygen and takes place quickly with high intensity such as sprinting, push-ups, pull ups, jumping rope, lifting weights and others. The exercise that is done can certainly result in changes due to exercise such as sweating, contractions, faster heart rate and so on. These changes are controlled by the autonomic nervous system.